Reynel developmental language scales (RDLS) : um estudo longitudinal em crianças usuárias de implante coclear - Fortunato-Queiroz, Carla Aparecida de Urzedo (Universidade Federal de São Carlos, 2007)
The objectives of this work were to analyze the language development of deaf children using a cochlear implant (CI) through a longitudinal study using the Reynell Developmental Language Scales (RDLS), to compare the performance of the deaf children to the performance of children with normal hearing, and to correlate it with the time of use of the CI. The participants were 17 6-year-old children with normal hearing and 9 deaf children using CI. The chronological age of the deaf children ranged from 4 to 8 years-old. The time of use of CI was, on average, 1 year 6 months at the 1st evaluation, 3 years 7 months at the 2nd evaluation, and 4 years 9 months at the 3rd evaluation. The deaf children were evaluated longitudinally through the RDLS, which is composed of the Verbal Comprehension Scale and Expressive Language Scale. The data were analyzed qualitatively and quantitatively. The implanted children showed progress of both their receptive and expressive abilities that were statistically significant but inferior to the children with normal hearing. In the verbal comprehension the differences between means and medians of scores of the deaf children and of the normal children were statistically significant. In the expressive language there was not a statistically significant difference. There was no correlation between the answers in both scales and the time of use of the CI for this group of deaf children, probably had to the reduced number of children of this group. The study proves the efficacy of the CI to the development of receptive and expressive language abilities and shows that the RDLS is effective in the longitudinal evaluation of deaf children using CI. Fortunato-Queiroz, C.A.U (2005) Reynell Developmental Language Scales (RDLS): Une étude longitudinale d´ enfants porteur de l´implant coclear. Thèse de Doctorat. Programme de Pós-Graduação dans Éducation Spéciale. Universidade Federal de São Carlos. São Carlos, SP
Keywords: Educação especial; Deficientes auditivos; Implante coclear; Linguagem expressiva; Linguagem receptiva; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL